CALIBRAÇÃO DE UM MODELO PREDITIVO PARA EFICIÊNCIA ENERGÉTICA EM EDIFÍCIOS DE ESCRITÓRIO - Lopes, Felipe; Silva, Verônica; Labaki, Lucila (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The seek to supply the world energy demand has stimulated not only the search for alternative sources but also energy efficiency of existing systems. As buildings have a great impact on energy consumption, simulation tools can help select the most suitable strategies towards environmental comfort and energy efficiency. The objective of this research was to calibrate the Rhinoceros-Grasshopper parameterization platform for energy efficiency and thermal comfort study for office buildings. This platform was linked to EnergyPlus for thermalenergetic simulations of the designed model. For calibration, BESTEST Case 600 was simulated, and the model adjusted to validate the test. The results were compared to those accepted from ASHRAE 140-2014. Results showed energy demand for cooling of 6.342 kWh and for heating of 4.089 kWh, this last one close to the test limit but out of the minimum value required. Thus, the calibrated model demonstrated that the Rhinoceros-Grasshopper parametric software can aid in the design decisions regarding issues of thermal comfort and energy saving, in addition to increasing the possible number of satisfactory solutions for architects and engineers.